Blending theories towards understanding and designing socio-technical scenarios - Prado, Alysson Bolognesi Prado; Baranauskas, Maria Cecília Calani Baranauskas (Teste, 2018)
To understand the interweaving of ubiquitous computer systems and their dynamic social relations different theoretical sources are necessary. Socially Aware Computing provides a deep understanding on how information systems emerge from and interact with the social context, whereas Actor-Network Theory represents a promising referential to explain how people and artifacts mutually actuate to render social structures. In this paper, we assess the paradigmatic compatibility of these two theories, proposing a blend, which provides a single basis to enrich the understanding of complex scenarios for designers of socially-aware technology, followed by an example of application in a real-world problem.